The effects of valproic acid on appetitive and aversive instrumental learning in adult rats - Orczyk, John J.; Banks, Melissa; Garraghty, Preston (Frontiers in Behavioral Neuroscience, 2014)
Antiepileptic medications are the frontline treatment for seizure conditions. However, these medications are not without cognitive side effects. Previously, our laboratory reported learning deficits in phenytoin and carbamazepine-treated rats. In the experiment reported here, the effects of valproic acid (VPA) have been studied using the same instrumental training tasks. VPA-treated rats displayed a severe deficit in acquiring a tone-signaled avoidance response. This deficit was attenuated in animals that had prior training in an appetitive context. Thus, this deficit is specific to learning in an aversive context, and does not result from difficulties in transferring associations from an appetitive to aversive context. Learning transfer deficits were previously observed in rats treated with phenytoin, and to a lesser extent, carbamazepine. On the other hand, rats treated with VPA fail to suppress inappropriate responsiveness across aversive training whether they had undergone prior appetitive training or not.